Implementing Nationally Determined Contribution Commitments in Agriculture (NDC4AG) Training package overview - Cramer, Laura K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Tri-fold brochure describing the training materials available online for implementing NDCs in the agriculture sector. The training materials were funded by Gesellschaft für Internationale Zusammenarbeit (GIZ) as part of the CAADP support programme with the African Union Development Agency (AUDA-NEPAD) and carried out in partnership with the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the Africa Group of Negotiators Expert Support (AGNES).